(untitled) (Scientific journal of the Fergana State University, 2023)
In modern linguistics, an important place is given to the study of linguistic aspects of interlingual speech activity, which is called "translation" or "translation activity". Translation today is an important method to facilitate the transfer of knowledge between languages ​​and cultures. In particular, an original translation, such as the one proposed, in which the translator does not have information about other translated versions as a precedent, is extremely important and complex. A text that is new to the language not only poses a unique challenge for the translator, but also represents a potentially interesting product for the reader.